Customer perceptions of mobile telecommunication providers in determining satisfaction and loyalty: focusing on college students - Simanjuntak, Ria Anggraini (Gema Wiralodra, 2023)
The increased demand for mobile services drives increasingly fierce competition among mobile telecommunications providers in Indonesia. New promotional strategies are needed, and companies are advised to determine the target group of customers to collect objective and adequate information regarding their real needs, such as college students. Therefore, this study examines college students' perceptions of adopting mobile telecommunication provider services in Indonesia. This study especially explains the effects of customer perceptions regarding service quality, price fairness, and brand image on satisfaction that leads to customer loyalty. A total sample of 208 customers of the mobile telecommunication providers in Java Island were randomly selected for the study, and the data collected was analyzed with CB-SEM. The empirical results revealed a positive significant impact of customer perceptions of service quality, price fairness, and brand image on customer satisfaction. College students’ perception of price fairness has the largest significant positive influence on customer satisfaction and loyalty. The mediation mechanism analysis also confirms that customer satisfaction partially mediates between customer perceptions of service quality and brand image. This study suggests that mobile telecommunication providers in Indonesia develop superior pricing strategies to increase customer satisfaction, leading to customer loyalty.Customer Perception